An optimized protocol for the preparation of blood immune cells for transmission electron microscopy - Nimshitha Pavathuparambil Abdul Manaph (17870420) (2023)
Transmission electron microscopy (TEM) is a powerful technique that enables visualization of structural details inside cells. Prior to TEM imaging, biological samples must undergo several preparation steps that are optimized according to the sample type. Currently, there are limited protocols for the preparation of blood samples for TEM imaging. Here, we provide a detailed step-by-step method for preparing blood samples for TEM imaging. This protocol enables robust visualization of the ultrastructures of blood immune cells. In addition, we describe the typical cellular features that can be used to distinguish between different immune cells in the blood, such as neutrophils, eosinophils, monocytes, and lymphocytes. This protocol is useful for studying ultrastructural changes in blood immune cells under various physiological and disease conditions. Other Information Published in: Micron License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.micron.2023.103517